Measurement of Elastic Strain Wave Propagation Velocity Using FRSGs along Metallic Rods Subjected to Impact Load - Sudarisman, Sudarisman (Jurnal Semesta Teknika, 2010)
The accuracy of foil resistance strain gauge (FRSG) for strain wave propagation measurement along metallic rods, i.e. aluminium, brass, copper and steel rods, subjected to impact load has been investigated. Hexagonal cross section of 5/8â sides Ã 6â long metallic rods have been selected for specimens. At a distance of 8â from one end of each rod, an EA-09-125AD-120 type foil resistance strain gauge with gauge factor of 2.105 and resistance of 120W was installed. The rods were then placed on a pair of supports and loaded at the other end surface with an impact loading generated using an impulse hammer. The set up was also instrumented with a typical potentiometer circuit as a signal transducer, and an oscilloscope for signal acquisition. The output signals were then analysed by comparing with their respective theoretical values. The result showed that these FRSGs had demonstrated high accuracy in signal sensing indicated by negligible discrepancies between experimental values on one hand and their respective theor etical values on the other hand.